The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00404-014-3287-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of labour induction in patients with a single previous Caesarean section: a proposal for a clinical protocol

Abstract: Uterine induction after a single Caesarean section with ocytocic infusion and amniotomy where the cervix is favourable does not appear to entail any significant added risk in terms of maternal or foetal morbidity. Foley catheter induction is a reasonable option if the cervix is not ripe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 23 publications
5
26
0
17
Order By: Relevance
“…18,19 Table 4 summarises the results of studies using Foley catheter for IOL in the presence of a caesarean scar. 14,[20][21][22][23][24] It appears that DBC achieved comparable vaginal delivery rate (60.2% vs 58.0%) and similar uterine rupture/dehiscence rate (0.85 % vs 0.65%). There was no case report of neonatal death in studies using DBC while there were two cases reported with Foley catheter.…”
Section: Discussionmentioning
confidence: 90%
“…18,19 Table 4 summarises the results of studies using Foley catheter for IOL in the presence of a caesarean scar. 14,[20][21][22][23][24] It appears that DBC achieved comparable vaginal delivery rate (60.2% vs 58.0%) and similar uterine rupture/dehiscence rate (0.85 % vs 0.65%). There was no case report of neonatal death in studies using DBC while there were two cases reported with Foley catheter.…”
Section: Discussionmentioning
confidence: 90%
“…A recent report by Lappen et al [38], which included 6,033 women attempting TOL after a prior Cesarean delivery, found that induction of labour in women with one prior Cesarean delivery was associated with an increased risk of failed VBAC as compared with expectant management. Another study indicated that induction after a single Cesarean delivery with oxytocin and amniotomy where the cervix is favorable is not associated with added maternal or fetal morbidity [39].…”
Section: Discussionmentioning
confidence: 99%
“…A taxa de parto vaginal foi menor do que a encontrada em outros estudos que utilizaram a sonda de Foley em mulheres com cesariana prévia, o qual variou entre 43,7 e 64,1% 16,17,20,21 . A alta incidência de cesáreas pode ter ocorrido em razão da nossa pequena amostra, bem como pela tendência de alguns plantonistas em realizar uma nova cesariana nas mulheres com cesariana prévia e também porque nossa principal indicação de indução do trabalho de parto foram as síndromes hipertensivas, que cursaram com seis pacientes submetidas à cesariana por picos hipertensivos.…”
Section: Discussionunclassified
“…Essa necessidade resolutiva dos plantonistas corrobora um estudo que sugere que a presença da sonda de Foley é um fator de risco isolado para uma nova cesariana 20 . Outras publicações observaram que pacientes com cesárea anterior que desencadearam o trabalho de parto espontâneo tiveram menores taxas de cesarianas, quando comparadas com mulheres que iniciaram a indução com sonda de Foley 10,20,22 . Destacamos que todas as nossas gestantes tiveram o trabalho de parto induzido com sonda de Foley, diferente dos estudos mencionados, que compararam a indução com o parto espontâneo.…”
Section: Intervalo Da Colocação Da Sonda E O Parto (Variação) (N=9) 4unclassified
See 1 more Smart Citation